An Overview on Lignocellulosic Fibers Ienforced Polymer Composite Materials - Redwan, Amamer; Badri, Khairiah Haji; Baharum, Azizah (Al-Nahrain Journal of Science, 2017)
In polymer science lignocellulosic fiber-reinforced polymer composite materials have appeared in a wide range area. The composite made from those varieties of materials are low density, low value, comparable certain properties, and most importantly they’re environmental friendly. Although a number of the properties linked to composites generated from oil palm fibers and polymers (namely, those that are accessible through commerce) display aspects of commonality when compared to conventional synthetic fiber composites, such properties depend to a significant degree on the extent to which the fibers and matrix phase is compatible with the capacity to absorb moisture. Importantly, this emerges as a key concern and, moreover, disadvantages of Lignocellulosic fibers polymer composites and studies have suggested that it has a considerable impact on the composites’ physical and mechanical properties. The central aim of the current paper is to provide an overview of the extant research relating to Lignocellulosic fibers reinforced polymer composites, and particular attention will be directed towards the physical structure and constituent chemical components of Lignocellulosic fibers.